Downregulation of TrkC Receptors Increases Dendritic Arborization of Purkinje Cells in the Developing Cerebellum of the Opossum, Monodelphis domestica - Tepper, Beata; Bartkowska, Katarzyna; Okrasa, Malgorzata; Ngati, Sonia; Braszak, Magdalena; Turlejski, Krzysztof; Djavadian, Ruzanna (Frontiers in Neuroanatomy, 2020)
In therian mammals, the cerebellum is one of the late developing structures in the brain. Specifically, the proliferation of cerebellar granule cells occurs after birth, and even in humans, the generation of these cells continues during the first year of life. The main difference between marsupials and eutherians is that the majority of the brain structures in marsupials develop after birth. Herein, we report that in the newborn laboratory opossum (Monodelphis domestica), the cerebellar primordium is distinguishable in Nissl-stained sections. Additionally, bromodeoxyuridine birthdating experiments revealed that the first neurons form the deep cerebellar nuclei (DCN) and Purkinje cells, and are generated within postnatal days (P) 1 and 5. Three weeks after birth, progenitors of granule cells in the external germinal layer (EGL) proliferate, producing granule cells. These progenitor cells persist for a long time, approximately 5 months. Furthermore, to study the effects of neurotrophic tropomyosin receptor kinase C (TrkC) during cerebellar development, cells were obtained from P3 opossums and cultured for 8 days. We found that TrkC downregulation stimulates dendritic branching of Purkinje neurons, which was surprising. The number of dendritic branches was higher in Purkinje cells transfected with the shRNA TrkC plasmid. However, there was no morphological change in the number of dendritic branches of granule cells transfected with either control or shRNA TrkC plasmids. We suggest that inhibition of TrkC activity enables NT3 binding to the neurotrophic receptor p75NTR that promotes dendritic arborization of Purkinje cells. This effect of TrkC receptors on dendritic branching is cell type specific, which could be explained by the strong expression of TrkC in Purkinje cells but not in granule cells. The data indicate a new role for TrkC receptors in Monodelphis opossum.